Macromol. Rapid Commun. 6/2013. Issue 6 (12th March 2013) - Oh, Joon Suk; Dang, Luong Nguyen; Yoon, Sung Woon; Lee, Pyoung Chan; Kim, Dong Ouk; Kim, Kwang Jin; Nam, Jae Do
<x xml:space="preserve">Abstract</x> Front Cover: A polymer microsphere, crosslinked and functionalized by amine, can be used as a solid‐state template for the synthesis of gold (Au) crystals in the form of either nanoparticles (NPs) or plates. The polymer microsphere acts as an internal template to cultivate Au NPs inside the microsphere or an external template to generate the singlecrystal plates depending on the critical concentration of gold ions. Further details can be found in the article by J. S. Oh, L. N. Dang, S. W. Yoon, P. C. Lee, D. O. Kim, K. J. Kim, and J. D. Nam* on page 504. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>